The Needs for Developing the Competence of Early Childhood Teachers in Schools under Khon Kaen Primary Educational Service Area Office 5 - Namwichit, Nongnoot; Rooyuenyong, Wichian (Journal of Graduate MCU KhonKaen Campus, 2025)
This study aimed to 1) study the current situation, the desirable condition of competency of early childhood teachers in schools under Khon Kaen Primary Educational Service Area Office 5, and 2) study the needs for developing competency of early childhood teachers in schools under Khon Kaen Primary Educational Service Area Office 5. The sample group consisted of 339 school administrators and teachers under Khon Kaen Primary Educational Service Area Office 5. The sample size was calculated using Taro Yamane formula (Taro Yamane, 1973) at a sampling error level of 0.05, using school-based stratified random sampling method. The research instrument was a 5-level rating scale questionnaire with content validity (Index of Consistency: IOC) of 0.81 and a reliability of 0.993. The statistics used to analyze data comprised frequency, percentage, mean, standard deviation, and PNI Modified Index. The study results were found that: 1. The current situation and the desirable condition of competency of early childhood teachers in schools under Khon Kaen Primary Educational Service Area Office 5, in overall, were rated at a high level. The overall desirable condition was rated at the highest level. 2. The needs for developing competency of early childhood teachers in schools under Khon Kaen Primary Educational Service Area Office 5, ranked in order of importance were as follows: The aspect with the highest need was curriculum and classroom management, followed by the ability to manage classroom and consistent and systematic learning plan design, respectively.